Behavioural intention to use facebook’s recommender system among students of STML UUM - Tang, Zhi Peng; Abdullah, Rohani (Universiti Utara Malaysia, 2020)
This research is based on an application of Big Data, which is Facebook’s recommender system. The objective of this research is to investigate the relationship of perceived ease of use, perceived usefulness, attitude and behavioural intention towards using Facebook’s recommender system. This study is using quantitative approach, by distributing to the students of STML UUM and the result is interpreted by using IBM SPSS version 25. The findings of this research found that students are reacting positively towards the usage of Facebook’s recommender system. It is hoped that the Facebook’s authority will be improving the privacies and confidentiality aspects of accessing Facebook’s user data